Hubungan kontribusi edukatif orang tua dan motivasi belajar dengan hasil belajar kognitif IPS peserta didik kelas iv sekolah dasar - Sari, Ayu Atika; Poerwanti, Jenny Indratoeti Siti; Sularmi, Sularmi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This study aims to 1) describe whether there is a relationship between the educational contribution of parents and social learning outcomes of fourth grade elementary school students; 2) describe whether or not there is a relationship between learning motivation and social studies learning outcomes of fourth grade elementary school students; and 3) describe whether there is a relationship between parents' educational contribution and learning motivation together with social studies learning outcomes of fourth grade elementary school students. A correlational study survey approach was used in this study. The population of this study were fourth grade students of a Public Elementary School in Laweyan District, Surakarta for the 2021/2022 academic year. The Probability Sampling approach was used to collect the sample. Data collection techniques with tests and questionnaires. Based on data analysis, 1) there is a positive and significant relationship between parental guidance and student social studies learning outcomes of 49.1 percent; 2) there is a positive and significant relationship between learning motivation and student social studies learning outcomes of 26.4 percent; and 3) there is a positive and significant relationship between parental guidance and learning motivation together with student social studies learning outcomes.